One Word - Yak Kaleme 19th-Century Persian Treatise introducing Western Codified Law - Seyed-Gohrab, Asghar (Iranian Studies Series, 2010)
"One Word - Yak Kaleme" is one of the first treatises in the Middle East to demonstrate that Islam is compatible with modern western forms of government, and specifically that sharia principles can be incorporated in a codified law comparable to that found in Europe. Unlike many fellow Oriental travellers, the author observed that European dominance is not derived from a few technological advances, but primarily from the organization of society. In "One Word", the author argues that the principles underlying constitutional government can be found in Islamic sources. "One Word" is a significant text during the Iranian Constitutional Revolution of 1906, but its message is relevant today.